Modular control of vertebrate axis segmentation in time and space - Seleit, Ali; Brettell, Ian; Fitzgerald, Tomas; Vibe, Carina Beatrice; Loosli, Felix; Wittbrodt, Joachim; Naruse, Kiyoshi; Birney, Ewan; Aulehla, Alexander (The EMBO journal, 2024)
How the timing of development is linked to organismal size is a longstanding question. Although numerous studies have reported a correlation of temporal and spatial traits, the developmental or selective constraints underlying this link remain largely unexplored. We address this question by studying the periodic process of embryonic axis segmentation in-vivo in Oryzias fish. Interspecies comparisons reveal that the timing of segmentation correlates to segment, tissue and organismal size. Segment size in turn scales according to tissue and organism size. To probe for underlying causes, we genetically hybridised two closely related species. Quantitative analysis in ~600 phenotypically diverse F2 embryos reveals a decoupling of timing from size control, while spatial scaling is preserved. Using developmental quantitative trait loci (devQTL) mapping we identify distinct genetic loci linked to either the control of segmentation timing or tissue size. This study demonstrates that a developmental constraint mechanism underlies spatial scaling of axis segmentation, while its spatial and temporal control are dissociable modules.
Online veröffentlicht: 9 August 2024
Gesehen am 08.04.2025